The Effect of Limited Time Offers and Platform Service Quality on Impulsive Buying Among E-Commerce Consumers in Indonesia With Paylater As a Moderating Variable - Nazmi Aulia Rachim; Sulhaini (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The rapid growth of e-commerce in Indonesia has led to the emergence of various digital marketing strategies that stimulate consumers’ impulsive buying behavior. This study examined the effects of limited time offers and platform service quality on impulsive buying among e-commerce consumers in Indonesia, with paylater as a moderating variable. It employed a quantitative approach. Research data were collected using an online survey method, in which questionnaires were distributed through social media. The collected data were analyzed using the Structural Equation Model (SEM) method with Amos 31 software. The results of this study indicate that limited time offers have a significant effect on impulsive buying. In contrast, platform service quality does not have a significant effect on impulsive buying. In addition, paylater has been shown to influence the relationship between limited time offers and platform service quality, as well as impulsive buying. This study contributes to the literature and has practical implications for e-commerce practitioners in developing digital marketing strategies.